Haematological observations on helminthiasis caused by Haemonchus contortus in Nigerian dwarf sheep - Anosa, V.O. (Springer, 1977)
The haematology of three groups, A, B and C, of unweaned lambs aged 2, 4 to 4½ and 5 to 6½ months respectively and their dams exposed to a natural outbreak of helminthiasis predominantly caused by Haemonchus contortus was studied prior to and after treatment with thiabendazole. Lambs of group A showed negative faecal egg counts and had normal red cell values and live weights. Lambs of groups B an C showed signs of severe parasitism including marked stunting and a normocytic normochromic anemia characterised by low packed cell volumes, low red cell counts and depressed haemoglobin concentrations; these lambs displayed marked individual variability in the effects of the disease, with very significant correlations (P < 0'01) between strongyle egg counts and red cell values. Severe anaemia was associated with a high reticulocyte response (2 to 16 per cent). Treatment with thiabendazole was followed by reduction of faecal egg excretion and significantly improved packed cell volumes and red cell counts but not haemoglobin concentration, as measured weeks later. The ewes were only mildly parasitised, with low faecal egg Counts and a mild depression of the red cell indices; these were slightly but significantly elevated following treatment. These findings are discussed in relation to observations in other parts of the world, to the Nigerian livestock management practices, and to the low hematological status commonly encountered in African livestock.